Effect of Dentine Pretreatment with 38% Silver Diamine Fluoride and CPP-ACPF on Micro-Shear Bond Strength of Resin Modified Glass Ionomer Cement - PhaniKumar, Mettapalli Sai; RojaRamya, Kakarla Sri; Vinay, C.; Uloopi, K.S.; Alla, Rama Krishna; Chaitanya, Penmatsa (Asian Journal of Chemistry, 2023)
The aim of the study is to evaluate the micro-shear bond strength and mode of failure of resin modified glass ionomer cement (RMGIC) placed on demineralized dentin pre-treated with 38% silver diamine fluoride (SDF) and casein phosphopeptide amorphous calcium phosphate (CPP-ACP). In order to mount the premolars in acrylic blocks, 30 caries-free human premolars were divided mesio-distally into two equal halves.. Then the enamel was removed to expose the dentin and immersed in demineralizing solution for 96 h, which were then randomly allocated into three groups: Group-1: pretreatment with 38% SDF + RMGIC; Group-2: pretreatment with CPP-ACPF + RMGIC; and Group-3: No pretreatment + RMGIC (control). After the pre-treatment, resin modified glass ionomer cement was placed over the dentin surface using cylindrical mold. Then the micro-shear bond strength was evaluated using universal testing machine and mode of fracture was analyzed with stereomicroscopy. The micro-shear bond strength was found to be higher for the control group (35.73 ± 4.15) followed by SDF (28.39 ± 1.64) and CPP-ACPF (23.00 ± 2.17) and this difference was found to be statistically significant (p = 0.001). On analyzing the mode of failure, the adhesive type of failure was most common in all the groups and the difference in the percentages of mode of failure between the groups was not significant (p = 0.337). Application of 38% SDF and CPP-ACPF on demineralized dentin samples has shown to reduce the micro-shear bond strength of resin modified glass ionomer cement. Adhesive failures were the most common type of failures in both pretreated and untreated groups.